Regulating Energy between Main Supply and Solar Energy Using Power Electronics Devices - Jamaludin, Muhammad Nizar (Universiti Teknologi Petronas, 2004)
The project title is Regulating Energy between Main Supply and Solar Energy Using PowerElectronics Devices. The aim is to design a regulating system between main supply and solar energy using power electronic devices. The study explored the implementation of several type of power electronics circuits such as rectifier circuit, filter circuit, regulator circuit and switching circuit. In the project process, Multisim2001 have been used as the simulation tools. Simulation process is a very important in order to test the operationof circuits and also to integrate between circuits. Ultiboard is another software that isused inthisproject. The software used to convert simulated circuit into PCB circuit. The process of conversion into PCB is done in the lab. For this project, the author has successfully produced the prototype for 15 V. The prototype has been tested and it works well. Besides, simulations for a circuit that can withstand 240 V also have been successfully simulated.